Enablers and inhibitors of vertical farming in urban Johannesburg, South Africa - Lowry, Joanne (My University, 2015)
ABSTRACT The world‘s growing population is placing ever more pressure on global food security. This situation is exacerbated by climate change, which is reducing the amount of arable land available for farming purposes and traditional farming‘s inability to operate without utilising large amounts of natural resources. Experts agree that over the next 50 years, traditional farming methods are going to be marginalised in favour of lower impact methods of food production. Vertical farming has been suggested as an alternative method of food production. Through this study the literature has been examined. The researcher interviewed both local and international experts in the fields of vertical farming and urban agriculture in order to deduce the enabling and inhibiting factors that would facilitate or hinder the development of vertical farming as a method of food production in urban Johannesburg. The correlation of the information from the literature review and the interviews that were conducted it showed that institutional structures, space and technical requirements would facilitate and enable the development of vertical farming and that knowledge gaps and the risks associated with farming in the urban environment would constitute as the main inhibiting factors that would limit the development of vertical farming in urban Johannesburg. The examination of the evidence in this study indicates that the benefits of vertical farming supported by institutional structures and existing technology, outweigh the risks associated with developing a new method of farming. This suggests that vertical farming could become a vehicle for the development of urban agriculture in urban Johannesburg, South Africa.
MBA 2015
Keywords: Urban agriculture -- South Africa -- Johannesburg,Vertical gardening,Food security